A Study of Effects of Uses Youtube Based Study Materials of Mathematics on the Academic Achievement of Students - Kumar, Rajeev (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Present era is Internet era. ICT (Information Communication and Technology) has become an integral part of all walks of life including Mathematics education. YouTube is an online video sharing service of Google. It is one the important tool of Web 2.0 technology. It can be integrated with classroom study materials for the larger benefits of the students. A study was carried out to investigate the effect of integrating YouTube contents with academic study materials of Mathematics on Academic Achievement of high school students. It was a quasiexperimental educational research, which was designed on the basis of Solomon Four Group. The total sample size was 44 high school students at Indore, in which 22 were in experimental group and 22 were in control group. Simple convenience random sampling technique was used to assign the four groups into experimental and control groups for the study. Researcher developed YouTube‘s video based study materials of Mathematics as per the syllabus of high schools. These study materials were used for treatment to the experimental groups. For collection of data on the academic achievement, Students‘ Achievement Test (SAT) was also developed by the researcher. Content and face validity was ensured with the help of experts. Reliability of the SAT was 0.89 using test-retest method.  Null hypothesis were formulated, which was tested on the basis of mean, standard deviation and t-test statistic calculated for the data collected on the basis of pre-test and post-test scores of the students in the SAT. It was found that experimental group had increased their achievement to a greater degree than the control group. Result of t-test concluded that difference between the academic achievements of experimental groups and control groups was significant at 0.05 level of significance and null hypothesis was rejected. The findings of the study demonstrated that YouTube based study materials is beneficial in improving academic scores in Mathematics of the students.